AI and corporeal knowledge: inventing and performing with prostheses and sonic organs - Marco Donnarumma; Marco Donnarumma (Frontiers in Computer Science)
The mainstream development of AI for artistic expression thrives on predictive models that are supposedly capable of abstracting creative ideas and actions into computable features. The assumption is that creativity can be measured, modeled, and computationally reproduced solely by examining digital representations of artistic outputs, such as images or pieces of music. Embodiment and its role in art and music making is largely ignored. But as any practicing artist knows, the act of creating an artwork and the fact of being a body are inseparable. This essay is concerned with nurturing a rapprochement of embodiment and AI in music and performing arts. To that end, it suggests it is necessary to transgress norms in engineering, musical composition, and bodily performance; to engage with modes of expression lying beyond the formal boundaries of those disciplines. The key questions are: What are the strategies needed to create embodied approaches to AI that can open up new areas of corporeal knowledge? How to create musical AI systems that allow to transgress musical and bodily borders, systems that allow learning beyond the edges of normative corporeal experience? These issues are broached by means of a transdisciplinary framework combining insight from feminist phenomenology, critical disability studies, and the posthuman with resources from physiological computing, movement-based music technology, and sound studies. Leveraging these assets, I offer an analysis of corporeal knowledge: a pre-cognitive form of perceiving and experiencing the world rooted in the somatics of incorporation, rhythm, and automaticity. Understanding this visceral way of knowing serves to discuss three strategies for transgression taken from my own artistic practice with robotics, prosthetics, sensors, and sound. By designing AI instruments and prosthetics that alter and are influenced by a performer’s somatic states, one can develop forms of artistic expression where body and instrument are co-dependent. I refer to this relation as a “configuration” of human and machine parts that, through training in sensorial and vibrational intensities, shapes not only music and performance but embodiment itself.